Andrographis paniculata restores gut health by suppressing inflammation and strengthening mucosal immunity - Tyagi, Vidushi; Kumar, Ashish; Shanker, Karuna; Pal, Anirban (Frontiers in Pharmacology, 2025)
BackgroundGut immunity plays a critical role in overall health by balancing tolerance to food antigens and microbiota while defending against pathogens. Inflammation and infection in the gut can disrupt this balance, leading to disease. Andrographis paniculata, a plant used in traditional medicine, is known for its anti-inflammatory and immune-modulating properties, making it a promising candidate for treating gut-related conditions.MethodsA. paniculata ethanolic extract (ApEtOH) was prepared by ethanol extraction of leaves, and bioactive compounds were identified using HPLC. Anti-inflammatory effects were evaluated in vitro using a Caco-2/RAW264.7 co-culture inflammation model via ELISA. Gene expression of chemokines in Caco-2 cells infected with Salmonella Typhimurium was assessed via quantitative real-time PCR. For in vivo studies, BALB/c mice were treated with ApEtOH at different doses, and the effects on bacterial load, immune response, and inflammation were assessed.ResultsApEtOH significantly downregulated the chemokines RANTES, MCP-1, and ENA-78, reducing the pro-inflammatory cytokines TNF-α and IL-6 in vitro. In vivo studies demonstrated reduced bacterial colonization in the spleen, lower systemic markers of infection, and restoration of intestinal homeostasis. ApEtOH normalized serum IgA, increased IgG, and decreased TNF-α and IL-10 levels. It also increased the expression of mucin (Muc-2) and lysozyme (Lyz-1), which are critical for epithelial integrity and antimicrobial defense.ConclusionApEtOH shows significant therapeutic potential for gut health by reducing bacterial colonization, modulating inflammation, and enhancing both innate and adaptive immunity. It may be a promising natural remedy for microbial induced gastrointestinal diseases and restoration of gut homeostasis.